Systematic review and meta-analysis of shenqi fuzheng and chemotherapy combination in the treatment of breast cancer (Bangladesh Journal of Pharmacology, 2016)
This review evaluates the effectiveness and safety of injection of shenqi fuzheng with chemotherapy in the treatment of breast cancer in China. The study included 20 randomized clinical trials (RCTs) involving 1,609 patients. It was shown that shenqi fuzheng could improved the treatment efficiency, Kamofsky Performance Status (KPS), weight and autoimmune; reduced fatigue, gastrointestinal reaction and the toxicity of bone marrow; protected liver, kidney and heart from damage by chemotherapy. However, the quality of all the studies was relatively low and there was great heterogeneity between various studies. Further well-designed research is needed to estimate the beneficial effects of shenqi fuzheng.